2023
DOI: 10.3390/su15118623
|View full text |Cite
|
Sign up to set email alerts
|

Tourist Behavior in the Cruise Industry Post-COVID-19: An Examination of Service Quality, Corporate Image, and Intentions to Pay and Revisit

Bodur S. Alonazi,
Thowayeb H. Hassan,
Mostafa A. Abdelmoaty
et al.

Abstract: The COVID-19 outbreak has had detrimental consequences on the cruise industry due to the suspension of commercial cruise trips, and these effects remain apparent in Saudi Arabia. The offered service quality (SQ) in the post-COVID-19 era seems to be a critical element for improving customer experiences and satisfaction, enhancing destination attractiveness, increasing revenue, and maintaining repeat business. The current study aimed to assess the impact of service quality on tourists’ satisfaction and corporate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 88 publications
(120 reference statements)
0
1
0
Order By: Relevance
“…In services, some studies recognised the indirect effect of service quality on behavioural intention, mediated by the satisfaction variable [41,46], and a variety of works have even shown that service quality directly influences customer behavioural intention [59][60][61]. In turn, some researchers have also revealed the existence of significant correlations and significant direct effects between the perceived quality and the customer's behavioural intention, in the nautical tourism segment [62], in the domain of sports [63] and education [42,43,45].…”
Section: Perceived Quality and Behavioural Intentionmentioning
confidence: 99%
“…In services, some studies recognised the indirect effect of service quality on behavioural intention, mediated by the satisfaction variable [41,46], and a variety of works have even shown that service quality directly influences customer behavioural intention [59][60][61]. In turn, some researchers have also revealed the existence of significant correlations and significant direct effects between the perceived quality and the customer's behavioural intention, in the nautical tourism segment [62], in the domain of sports [63] and education [42,43,45].…”
Section: Perceived Quality and Behavioural Intentionmentioning
confidence: 99%